(3 + 1)-formulation for gravity with torsion and non-metricity: the stress–energy–momentum equation. (5th July 2021) - Ariwahjoedi, Seramika; Suroso, Agus; Zen, Freddy P
Abstract: We derive the generalized Gauss–Codazzi–Mainardi (GCM) equation for a general affine connection with torsion and non-metricity. Moreover, we show that the metric compatibility and torsionless condition of a connection on a manifold are inherited to the connection of its hypersurface. As a physical application to these results, we derive the (3 + 1)-Einstein field equation (EFE) for a special case of metric-affine f R -gravity when f R = R, the metric-affine general relativity (MAGR). Motivated by the concept of geometrodynamics, we introduce additional variables on the hypersurface as a consequence of non-vanishing torsion and non-metricity. With these additional variables, we show that for MAGR, the energy, momentum, and the stress–energy part of the EFE are dynamical, i.e., all of them contain the derivative of a quantity with respect to the time coordinate. For the Levi–Civita connection, one could recover the Hamiltonian and the momentum (diffeomorphism) constraint, and obtain the standard dynamics of GR.